La cité d’expériences à l’épreuve d’une traduction par le design - Caroline Bougourd (Appareil)
The cité d’expériences of Noisy-le-Sec is a landmark of the building industrialization policy led by the Ministry of Reconstruction and Urban Planning. Considered an experimental site created at the end of the Second World War, its program was to design a district of prefabricated houses filled with urban, architectural and social innovations. Today, the site is listed in the additional inventory of Historic Monuments. Replacing the notion of transmitting a heritage by the idea of translating a memory leads us to question the sustainable hypotheses as to the future of such a neighborhood once again. The concept of translation turns language into its own medium and consists of mediating an original statement with constantly renewed proposals because of their inability to join perfectly and sustainably to a sense. Looking at the cité from this translation point of view, makes it possible to think about an alternative between preservation, conservation and restoration. We will study various forms of memory translation : historical translation and heritage translation. In parallel, we sought to offer an alternative through design, based on the idea that the translation of the cité d’expériences should be both educational and fed by contradictory testimonies, in order to highlight the controversy through it. Regarding this, we will present the project of an interactive digital story questioning such peculiar heritage controversy (http://unebaladeaumerlan.fr/). According to us, this project can be regarded as a didactic translation of a specific history through design. The aim of this article is to rely on a concrete case to highlight what translation as a way of thinking by design can bring up in our project behaviors in keeping with our environment. What changes when the designer becomes a translator ?